Hilah Hukum dan Kemungkinan Penerapannya dalam Praktik Hibah dan Wasiat - Jannah, Elly Uzlifatul; Faizah, Isniyatin (Program Studi Hukum Ekonomi Syariah, 2023)
The Islamic law is god’s regulation for human advantages in the word and hereafter. It always relevant with the situation and more elastice toward the mua’amalah (furu’iyah) cases. But the elasticity of the Islamic law always be politicized to obtain the self-interest with out any concider the wors result. Exemple, something (regulation) that forbid by Nash would be allowed immediately because of interest. In Islamic law this case is mentioned as Hilah. Hilah is forbidden by syar’i, but in Islam, part of people are allowed and forbid the hilah. Hilah is suppose as an action to avoid the Islamic law subtantially that contain the moral value, meanwhile the is may not abolished in aplication of law. Hilah is one of the way to finding and developing Islamic law in every cases. It make Islamic law can be always relevant with every situation, no one left behind. For example Hibah and Wasiat for a daughter, one of the strategy to deviding the heir propotion without seeing a gender between a male or fimale. It has a wisdom legal fiction to finding the moral value, not a hilah to avoidding the religion obligations that was absolute in justice.